Developing a family-level intervention for families of children with cancer. - Svavarsdottir EK; Sigurdardottir AO (Oncology Nursing Forum, 2006)
PURPOSE/OBJECTIVES: To determine the feasibility and effectiveness of a family-level intervention for parents of children newly diagnosed with cancer. DESIGN: A one-group, pretest and post-test, quasi-experimental design. SETTING: A university hospital in Iceland. SAMPLE: 10 families (19 parents) of children and adolescents newly diagnosed with cancer. METHODS: Parents were asked to answer questionnaires at baseline and then twice after the intervention, at 6 and 12 months. MAIN RESEARCH VARIABLES: Acceptability and short-term effects on parents' well-being, coping behavior, hardiness, and adaptation of an educational and informational home page, support offered on the Internet to parents, and one or two 60- to 90-minute support interviews. FINDINGS: Most of the families indicated that the intervention was important, helpful, and supportive, but the level of usefulness of the intervention varied. Information from the hypotheses testing, that parents' level of well-being increased significantly one month after the intervention and that fathers found it helpful to maintain social support and psychological stability after the intervention, are optimistic indicators and support a possible short-term effect of the intervention. CONCLUSIONS: Offering a family-level educational and support intervention was feasible and may be effective for such families. IMPLICATIONS FOR NURSING: Researchers and clinicians may want to enhance the intervention and test it on bigger samples and with a control group.